The European dream : how Europe's vision of the future is quietly eclipsing the American dream - Rifkin, Jeremy (Cambridge : Polity, 2005)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: levensstandaard; economische ontwikkeling; Europa; Verenigde Staten van Amerika